Pancreatic solid pseudopapillary neoplasm, rare presentation in pediatric age group: two case reports - Alshawwa, Khaled; Njoum, Yumna; Abdul-Hafez, Hamza A.; Bannoura, Sami; Abukeshek, Tawfiq; Ashhab, Hazem; Abu-Zaydeh, Omar (Frontiers in Oncology, 2025)
Solid pseudopapillary neoplasm (SPN) is a rare tumor that primarily affects young females. It is typically found in the pancreas and is often asymptomatic until it grows to a large size. SPN is more frequently located in the body or tail of the pancreas in adults, whereas in children, it is more commonly found in the head of the pancreas. In this report we present two female patients in the pediatric age group who were diagnosed with pancreatic SPN, each presenting with nonspecific symptoms, one with recurrent epigastric pain and nausea, the other with carpopedal spasms. Imaging showed large, cystic-solid pancreatic masses in both. Each case underwent a Whipple procedure (pancreaticoduodenectomy) with R0 resection. Pathology confirmed SPNs without lymphovascular or perineural invasion, and all surgical margins were clear. This series underscores SPN’s varied presentations and favorable surgical outcomes in young adolescents. SPN is a rare neoplasm with low malignant potential that can present as a large abdominal mass. Although surgical resection is the treatment of choice, the optimal surgical approach remains controversial. Early detection and timely management are essential for a favorable outcome. Clinicians should consider SPN in the differential diagnosis of young females presenting with epigastric or pancreatic masses. This report highlights the importance of early detection and timely management of SPN.